Employee retention: a study in Malaysian Palm Oil Board / Nur Hazimah Ahmad Zubir and Nur Farah Hanna Md Shaari - Ahmad Zubir, Nur Hazimah; Md Shaari, Nur Farah Hanna (Faculty of Business and Management, 2016)
This research aims to examine the relationship between the factors which will affect employee retention among employees in Malaysian Palm Oil Board (MPOB). The factors includes compensation, training and development, supervisor support and work environment. Throughout this research, the researchers also aim to find out the most influence factors over employees retention in MPOB. Each of these factors will be tested to determine the relationship with the employee retantion. The results of the relationship were obtained by the questionnaires answered by the respondent. All the questionnaires were adopted from the past research. The questionnaires were distributed to employees who are currently working in the Headquaters of Malaysian Palm Oil Board in the Department of Finance and Management only. 108 respondents were participated in the survey conducted. The demographic informations about the respondents has been analyzed and converted into Frequency Analysis. There were three hypotheses generated and tested using the Descriptive Analysis, Pearson’s Correlation and also Multiple Regression. All the data obtained were generated by the IBM SPSS. The researchers found that all the factors choosen have a significantly relationship with the employee retention. The findings of this research indicate that employees in MPOB found that training and development is the most effective factors that influence them to retain in the organization. The results of these findings were discussed and there are some recommendations proposed for the future study.